BAEL PRESERVE-SYRUP AS BOOSTER OF HUMAN HEALTH AS A HEALTH DRINK - SINGH, AMIT KUMAR; I. CHAKRABORTY,; A. K. CHAURASIYA, (The Bioscan, 2014)
The experiments were carried out in the Laboratory of Post Harvest Technology, Research Complex, Kalyani (Bidhan Chandra Krishi Viswavidyalaya) West Bengal during the year 2008-2010 to assess the physico-chemical characteristics and sensory attributes of fresh fruit and its processed product. The two cultivars of bael viz., Local cultivar of West Bengal and NB-5 were used for this experiment. Fruits of both cultivars were large in size and greenish yellow to yellowish green in colour. The average fruit weight (723.50 and 1212.50 g), pulp per cent (75.40 and 79.62), TSS (12.2 and 14.4 ºBrix), ascorbic acid (13.12 and 27.36 mg/100 g pulp) and ² carotene (1868.01 and 1155.37 IU) were obtained from freshly harvested of fruits. The fruit slices were dipped in alum solution (2 per cent) for two hours and it’s blanched. The bael preserve syrup was prepared with the combination of sugar, acid, water and preservative. The recipe of bael preserves syrup was found best and it was stored at room (25-37ºC) and refrigerated temperatures (8-10ºC) up to 8-12 months as well as organoleptic score 4.64 and 4.88 was found best among all treatments of local and NB-5 cultivars respectively.